2010
DOI: 10.1039/b9nr00224c
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting tantalum disulfide nanotapes; growth, structure and stoichiometry

Abstract: Superconducting tantalum disulfide nanowires have been synthesised by Surface Assisted Chemical Vapour Transport (SACVT) methods and their crystal structure, morphology and stoichiometry studied by powder X-ray diffraction (PXD), scanning electron microscopy / energy 10 dispersive X-ray spectroscopy (SEM, EDX), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and nanodiffraction. The evolution of morphology, stoichiometry and structure of materials grown by SACVT methods in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…[26][27][28] But the remarkable difference is that the I-II isosymmetric transition in In 2 Se 3 leaves crystal symmetry unaffected, whereas the polytypic transitions in SiC and TaS 2 result in the change of space group.…”
mentioning
confidence: 99%
“…[26][27][28] But the remarkable difference is that the I-II isosymmetric transition in In 2 Se 3 leaves crystal symmetry unaffected, whereas the polytypic transitions in SiC and TaS 2 result in the change of space group.…”
mentioning
confidence: 99%
“…Previously, it has been demonstrated that the use of a pinched tube can significantly enhance the yield of nanofibrous products grown using chemical vapor transport reactions,22, 23 indicating that the flow dynamics within such a system play an important role in the formation of these nanostructures. We therefore considered how this approach could be implemented for the controlled growth of ZnO nanostructures, and how specific parameters affect the formation and resultant morphology of the final products.…”
Section: Resultsmentioning
confidence: 99%
“…and has since been adopted as a reliable method by a number of other groups 12, 13. In other work, modification of the reaction tube by creation of a pinch or constriction between the solid precursors and the substrates has been shown to aid the morphological tuning of products, and their yields, for a number of different materials including TaS 2 nanowires, ribbons, and belts 22, 23. To the best of our knowledge, the combination of the inner tube “pinch” restriction and the double tube set‐up for the synthesis of ZnO nanostructures is unique, and thus we report here a new, modified quartz‐tube design in a horizontal, double‐tube, deposition system.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures like carbon nanotubes or semiconducting quantum dots have already been developed for use in a wide variety of applications (Derycke et al, 2001;Dunnill et al, 2009;Martel et al, 1998;Michalet et al, 2005;Tans et al, 1997). As part of the development of these materials, it is important to develop new techniques for their assessment.…”
Section: Introductionmentioning
confidence: 99%